2008
DOI: 10.1158/1055-9965.epi-08-0443
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Transferases and Glutathionylated Hemoglobin in Workers Exposed to Low Doses of 1,3-Butadiene

Abstract: We evaluated glutathione transferase (GST) activities and the levels of glutathionylated hemoglobin in the RBC of 42 workers exposed to 1,3-butadiene in a petrochemical plant, using 43 workers not exposed to 1,3-butadiene and 82 foresters as internal and external controls, respectively. Median 1,3-butadiene exposure levels were 1.5, 0.4, and 0.1 Mg/m 3 in 1,3-butadieneexposed workers, in workers not directly exposed to 1,3-butadiene, and in foresters, respectively. In addition, we determined in the peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…The values measured are also lower than those measured in dialyzed (5% -20%; weighted mean 11.4%) [13,18] and diabetic (5% -11%; weighted mean 8.3%) [16,17,20] subjects and, for the group of smokers, approximately in the same range (7.2% ± 2.8%) of healthy subjects who are occupationally exposed to butadiene in chemical plants at airborne concentrations in the range 0.1 -200 μg/m 3 [19].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The values measured are also lower than those measured in dialyzed (5% -20%; weighted mean 11.4%) [13,18] and diabetic (5% -11%; weighted mean 8.3%) [16,17,20] subjects and, for the group of smokers, approximately in the same range (7.2% ± 2.8%) of healthy subjects who are occupationally exposed to butadiene in chemical plants at airborne concentrations in the range 0.1 -200 μg/m 3 [19].…”
Section: Discussionmentioning
confidence: 59%
“…A total number of subjects approaching one thousand have been examined. The results of the studies published in the literature are collected in Table 1 (see references [12][13][14][15][16][17][18][19][20][21][22][23] therein).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, genetic and nutritional susceptibility factors could be relevant for TASH just as they are in ASH and NASH (11, 19). Genetic polymorphisms in enzymes implicated in the metabolism of industrial chemicals (cytochrome P450 2E1, or Cyp2E1, and glutathione S-transferases, or GST) influenced chemical toxicity in previous studies (29, 30). Importantly, the 30% prevalence of suspected TASH in our study is similar to the previously reported prevalence of GST polymorphisms in white populations (20–45%) (31).…”
Section: Discussionmentioning
confidence: 89%
“…Our data indicate that neither inhibition of DNA methyltransferases, nor 1,3butadiene-induced genotoxic alterations, except in the lung of female mice, could explain the loss of cytosine DNA methylation in the liver and lung of C57BL/6J mice. This indicates that disruption of other molecular pathways such as mitochondrial dysfunction (Hartman et al 2017) and 1,3-butadiene-induced oxidative stress (Primavera et al 2008;Zhang et al 2015), known factors that cause cytosine DNA hypomethylation (Valinluck et al 2004), or alterations in one-carbon metabolism and tricarboxylic acid cycle, may cause loss of DNA methylation in the liver and lung of C57BL/6J mice.…”
Section: Discussionmentioning
confidence: 99%